-4(-d-4)=-4+6(2d+6)

Simple and best practice solution for -4(-d-4)=-4+6(2d+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-d-4)=-4+6(2d+6) equation:



-4(-d-4)=-4+6(2d+6)
We move all terms to the left:
-4(-d-4)-(-4+6(2d+6))=0
We add all the numbers together, and all the variables
-4(-1d-4)-(-4+6(2d+6))=0
We multiply parentheses
4d-(-4+6(2d+6))+16=0
We calculate terms in parentheses: -(-4+6(2d+6)), so:
-4+6(2d+6)
determiningTheFunctionDomain 6(2d+6)-4
We multiply parentheses
12d+36-4
We add all the numbers together, and all the variables
12d+32
Back to the equation:
-(12d+32)
We get rid of parentheses
4d-12d-32+16=0
We add all the numbers together, and all the variables
-8d-16=0
We move all terms containing d to the left, all other terms to the right
-8d=16
d=16/-8
d=-2

See similar equations:

| 9x+3(2x-4)=18 | | (8)^x-5=512 | | 3(y+1)+2y=5(y-1)=5 | | 13x+21/7=16 | | 3(x+4)+2=8-(6-x) | | -66-6x=54 | | 3x/10-3x+4/5=3/5 | | 2(x+16)=100 | | 6x+2-x=37 | | 4x-4(2x+12)=-12 | | 5+u=4 | | 1/2(6x-4)=3x+2 | | 3x+4(-4x-6)=119 | | 3x+4(-4x6)=119 | | 3/9p=9 | | -3(x+4)=-2x+1 | | (3/10)x-3x+(4/5)=(3/5) | | 4x+8x-57=38-7 | | x-(15x-6)=107 | | 6x+3(3x+22)=216 | | 517=83-x | | 5c=c | | 517=83-c | | 85-4x=75-3.5x | | -8(7x+31)=-976 | | x+6/5-x-3/7=12/7 | | 7x+3(4x/)=109 | | 162-12x=-20x-246 | | -1x+1(x-1)=2 | | 60=2/3x+x | | 5(x-9)=35-3x | | (3x+33)(2x-3)=180 |

Equations solver categories